The Anatomy of Market Failure - Bator, Francis M. (Quarterly Journal of Economics, 1958)
Introduction, 351. — I. The conditions of market efficiency, 353. — II. Neoclassical external economies: a digression, 356. — III. Statical externalities: an ordering, 363. — IV. Comments, 371. — V. Efficiency, markets and choice of institutions, 377.